2014
DOI: 10.5812/ijhrba.16265
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies in People Attempting Suicide

Abstract: Background:Having a set of effective coping skills can prevent suicidal behavior by increasing self-control and self-direction. This study examines coping styles used by suicidal patients.Objectives:The researchers in this study try to identify coping strategies used by suicide attempters admitted to Shiraz Shahid Faghihi Hospital emergency room.Materials and Methods:This is a analytical cross-sectional study. Participants consisted of 50 suicide-attempted people admitted to Shiraz Faghihi Hospital. Instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 7 publications
2
29
0
Order By: Relevance
“…(20,21) Individuals who reported not having a partner used more coping strategies than those who did; however only positive reappraisal had significant association (p = 0.024). These results corroborate another study about coping by patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…(20,21) Individuals who reported not having a partner used more coping strategies than those who did; however only positive reappraisal had significant association (p = 0.024). These results corroborate another study about coping by patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 94%
“…Higher levels of education can have a positive influence on coping with stressful situations, helping the individual choose the focus of the problem. (20,21) The highest scores reported by subjects in relation to work shift were functional, regardless of the time working in the unit. However, there was no significant association among professional category, work shift, and different coping strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to medical, health, economic, social, and legal problems caused by drug abuse, the society needs to seriously pay more attention to effective preventive strategies (12,13). Choosing the right strategy to deal with mental pressures can be effective in decreasing the effect of these pressures on phys- ical and psychological heath of the patients (14,15). One of the strategies proposed by the researchers is life skills training.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have gained a great insight by examining coping styles of successful and unsuccessful individuals. They have found that people who manage problems successfully usually have equipped themselves with a variety of coping skills, and life skills training adds to one's coping skills (15,16,25,27). World Health Organization (WHO) has listed these skills along with introducing actual practices.…”
Section: Introductionmentioning
confidence: 99%